Physiological Aspects of Yield Variation among Seven Groundnut Genotypes Cultivated under Rain-Fed Conditions - Mohammed, Yasir E; El Naim, Ahmed M; Ahmed, Tarig E; Sulaiman, Abdelatif A; Bakhit, Omer A; Ibrahim, Khalid A (International Journal of Sustainable Agricultural Research, 2019)
A field experiment was conducted at two locations, in North Kordofan under rainfed conditions for two consecutive seasons (2005/06 and 2006/07), to study the physiological aspects of yield variation among seven groundnuts (Araichis hypogaea L.), genotypes (Barberton, Sodiri, Gubiesh, ICGV89171, ICGV93296, ICGV86744 and ICGV92126). The parameters related to morpho-physiological traits were measured: growth rate (CGR), relative growth rate (RGR), specific leaf area (SLA), net assimilation rate (NAR), leaf area (LA), leaf area (LAI) and yield. The results of the combined analysis showed that there were no significant (p =0.05) differences among varieties for the measured morpho-physiological traits throughout the season. Mean seasonal pattern of these traits indicated that the maximum LAI, SLA, CGR, RGR and NAR were attained 65 days after planting. Significant varietal differences were observed for pod yield, hay yield, 100-seed weight and pod maturity. The highest pods yields of 551, 545 and 540 kg ha-1 were recorded by Barberton, ICGV89171 and Sodiri, respectively.